Loading [MathJax]/jax/output/HTML-CSS/jax.js

Supplement to Frege's Theorem and Foundations for Arithmetic

Proof That No Number Ancestrally Precedes Itself

We wish to prove:

Lemma: No Number Ancestrally Precedes Itself
x[Nx¬Precedes(x,x)]

Proof. Assume Nb, to show: ¬Precedes(b,b). Now Fact 7 concerning R+ is:

[Fx&R+(x,y)&Her(F,R)]Fy

So we know the following instance of Fact 7 is true, where x=0, y is b, F is [λz¬Precedes(z,z)], and R is Precedes:

[λz¬Precedes(z,z)]0&Precedes+(0,b) &Her([λz¬Precedes(z,z)],Precedes))[λz¬Precedes(z,z)]b

By λ-Conversion on various terms in the above, this reduces to:

[¬Precedes(0,0)&Precedes+(0,b) &Her([λz¬Precedes(z,z)],Precedes)]¬Precedes(b,b)

So to establish ¬Precedes(b,b), we need to show each of the following conjuncts of the antecedent:

  1. ¬Precedes(0,0)
  2. Precedes+(0,b)
  3. Her([λz¬Precedes(z,z)],Precedes)

To prove (a), note that in the Proof of Theorem 2 (i.e., ¬x(Nx&Precedes(x,0))), we established that ¬x(Precedes(x,0)). But it is an instance of Fact 4 concerning R, that

xPrecedes(x,0)xPrecedes(x,0).

It therefore follows that ¬x(Precedes(x,0)). So ¬Precedes(0,0).

We know (b) by our assumption that Nb and the definition of N.

To establish (c), we have to show:

x,y(Precedes(x,y)([λz¬Precedes(z,z)]x[λz¬Precedes(z,z)]y))

That is, by λ-Conversion, we have to show:

x,y(Precedes(x,y)(¬Precedes(x,x)¬Precedes(y,y)))

And by contraposition, we have to show:

x,y(Precedes(x,y)(Precedes(y,y)Precedes(x,x)))

So assume Precedes (a,b) and Precedes(b,b). If we show Precedes(a,a), we are done. We know the following instance of Fact 8 concerning R+, where a is substituted for z, b for y, b for x, and Precedes for R:

Precedes(b,b)&Precedes(a,b)&Precedes is 1-1 Precedes+(b,a)

Since we have assumed Precedes(b,b) and Precedes(a,b), and we have proven in the main text that Predecessor is 1-1, we can use the instance of Fact 8 to conclude Precedes+(b,a). But the following is an instance of Fact 2 concerning R+, when a is substituted for x, b for y, a for z, and R is Precedes:

Precedes(a,b)&Precedes+(b,a)Precedes(a,a)

But we know Precedes(a,b) by assumption and we have just shown Precedes+(b,a). So Precedes(a,a), and we are done.

Proof of the Lemma on Predecessor

Copyright © 2017 by
Edward N. Zalta <zalta@stanford.edu>

This is a file in the archives of the Stanford Encyclopedia of Philosophy.
Please note that some links may no longer be functional.
[an error occurred while processing the directive]